Zintegrowane podejście w nauczaniu języka obcego - Antoni Paliński (Studia Rossica Posnaniensia)
This article deals with two of the four primary language skills – listening and reading. The author tries to show not only differences but also similarities between these two receptive language skills, as research has shown that they are very close to one another and have much in common, especially in terms of psychological aspects. The author draws readers’ attention to the fact that both processes – listening and reading – are connected with acquiring and understanding information, entail a critical and creative interpretation of a given text, have similar structure as well as require much concentration and ability to read between the lines, and, furthermore, to understand what is not said or written directly. It is suggested that an integrated approach should be incorporated into the foreign language teaching process, as there are clear similarities between the two aforementioned language skills, especially in the psychological dimension.